(untitled) (Bioresearch Communications, 2021)
Fifty six spotted rice grain samples of four commercially cultivated rice varieties namely BRRI 28, 29, Kalijira and Pajam were collected from 14 different districts of Bangladesh. Forty rice samples (Hybrid 2,3,4, BR7,11,12,14,16,22,23,25,26and BRRI28 to BRRI 55) were also collected from Bangladesh Rice Research Institute at Joydevpur. Twenty-fivespecies of fungi belonging to 15 genera were associated with these rice varieties. The isolated fungi were Alternaria alternata, Aspergillus clavatus, A. flavus, A. fumigatus, A.niger, A. ochraceus, A.oryzae, A. terreus, Chaetomium globosum, Cladosporium cladosporioides, Colletotrichum gloeosporioides, Curvularia lunata, C. lunata var. aeria, Drechslera oryzae, Fusarium moniliforme, F. oxysporum, F. solani, Microdochium oryzae, Nigrospora oryzae, Penicillium spp., Pestalotiopsis guepinii, Sarocladium oryzae and Trichoderma viride. Amongst these fungi nine i.e. Alternaria alternata (Fr.) Keissler, Aspergillus flavus Link, Curvularia lunata (Wakker) Boedijn, Drechsler aoryzae Breda de Haan (Subramanian and Jain), Fusarium moniliforme Sheldon, F. solani (Mart.) Sacc., Microdochium oryzae (Hashloka and Yokogi) Sam. and Hal., Pestalotiopsis guepinii (Desm.) Stay. and Sarocladium oryzae (Sawada) W. Gams and D. Hawks were found to be pathogenic to rice seeds. The most predominant fungus was D. oryzae which was followed by A. flavus and the least incidence was observed in case of F. solani and P. guepinni. Bioresearch Commu. 7(1): 932-940, 2021 (January)